The future of the Internet : and how to stop it - Zittrain, Jonathan (Yale University Press, 2008)
This extraordinary book explains the engine that has catapulted the Internet from backwater to ubiquity-and reveals that it is sputtering precisely because of its runaway success. With the unwitting help of its users, the generative Internet is on a path.